2010
DOI: 10.1038/sj.bjc.6605612
|View full text |Cite
|
Sign up to set email alerts
|

Mitogen-activated protein kinase phosphatase-1 (MKP-1) impairs the response to anti-epidermal growth factor receptor (EGFR) antibody cetuximab in metastatic colorectal cancer patients

Abstract: BACKGROUND: The validation of KRAS mutations as a negative marker of response to anti-epidermal growth factor receptor (EGFR) antibodies has meant a seminal advance towards treatment individualisation of colorectal cancer (CRC) patients. However, as a KRAS wild-type status does not guarantee a response to anti-EGFR antibodies, a current challenge is the identification of other biomarkers of response. On the basis of pre-clinical evidence, we hypothesised that mitogen-activated protein kinase phosphatase-1 (MKP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 55 publications
0
13
0
Order By: Relevance
“…Figure 1B is consistent with this hypothesis since cetuximab leads to activation of p38 and JNK. In agreement with this explanation, Montagut et al (2010) demonstrated in 2010 that MKP-1 overexpression impairs the response to cetuximab in mCRC patients. Our interpretation could be that overexpression of MKP-1 inhibits p38 activity and then prevent cetuximab maximal effect.…”
Section: Discussionmentioning
confidence: 63%
“…Figure 1B is consistent with this hypothesis since cetuximab leads to activation of p38 and JNK. In agreement with this explanation, Montagut et al (2010) demonstrated in 2010 that MKP-1 overexpression impairs the response to cetuximab in mCRC patients. Our interpretation could be that overexpression of MKP-1 inhibits p38 activity and then prevent cetuximab maximal effect.…”
Section: Discussionmentioning
confidence: 63%
“…In light of cytokine and chemokine findings discussed above, implications of these studies may extend well beyond HNSCC, as DUSP1 expression has been shown to be dysregulated in other cancers, such as breast, and may be predictive of response to targeted therapies, such as cetuximab (7,17). Genomic studies have not identified a common mutation or deletion, but a recent DNA methylation screen identified significantly increased promoter hypermethylation in over 80% of oral cancer tissues (18).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, DUSP4 and DUSP6 were originally identified as top resistance markers to cetuximab in unselected patients and the use of a four-gene expression model, including AREG, EREG and DUSP6 (as well as SLC26A3 -solute carrier family 26 member 3) has been shown to improve the identification of responders among pre-selected KRAS WT mCRC (9,11). Recently, Montagut et al have revealed that DUSP4 protein can be considered a promising negative marker of response to cetuximab-based treatment in mCRC with WT KRAS (17). When they assessed DUSP4 expression by immunohistochemistry in a small series of mCRC patients, overexpression of DUSP4 protein significantly associated with lower response rates and shorter median time to progression among KRAS WT patients (17).…”
Section: 'The Presence Of a Wild-type Kras Does Not Predict Response mentioning
confidence: 99%
“…Recently, Montagut et al have revealed that DUSP4 protein can be considered a promising negative marker of response to cetuximab-based treatment in mCRC with WT KRAS (17). When they assessed DUSP4 expression by immunohistochemistry in a small series of mCRC patients, overexpression of DUSP4 protein significantly associated with lower response rates and shorter median time to progression among KRAS WT patients (17).…”
Section: 'The Presence Of a Wild-type Kras Does Not Predict Response mentioning
confidence: 99%